Short-term family-centered workshop for children with developmental delays enhances family functioning and satisfaction: A prospective clinical trial. Issue 31 (August 2016) - Hsieh, Ru-Lan; Hsieh, Wen-Huei; Lee, Wen-Chung
Abstract : Abstract: We investigated the clinical efficacy on family functioning and parental satisfaction of a short-term family-centered workshop for children with developmental delays. A total of 32 children with developmental delays and their parents participated in 2-hour weekly group therapy sessions over 6 weeks. The workshop was conducted by rehabilitation professionals and teachers using a family-centered multidisciplinary approach. Both before and after the 6-week workshop, the parents were administered the Pediatric Quality of Life Inventory (PedsQL) Family Impact Module, the PedsQL Healthcare Satisfaction Module, the Hospital Anxiety and Depression Scale, and the World Health Organization Quality of Life brief assessment instrument. Overall satisfaction with the workshop was also evaluated. Significant improvements were noted in physical aspect ( P  = 0.03), communication ( P  = 0.002), and daily activities ( P  = 0.04) in the PedsQL Family Impact Module, and in communication ( P  = 0.03) and technical skills ( P  = 0.05) in the PedsQL Healthcare Satisfaction Module. Overall satisfaction with the workshop was rated as very high. There was no significant effect on psychological distress or quality of life. Short-term family-centered workshops for children with developmental delays improved family functioning and the parental perception of satisfaction, including health care satisfaction.